Prevalence of depression and anxiety disorders among bariatric surgery patients - Sait, Salma; Trabulsi, Nora; Zagzoog, Mohammad; Mortada, Hatan; Altowaireb, Afnan; Hemdi, Alyaa; Nassif, Mohammed; Altaf, Abdulmalik (Journal of Surgery and Medicine, 2019)
Aim: Obesity carries with itself an increased risk of psychological distress, depression and anxiety. Several studies have proven that the best modality of treatment for morbid obesity is bariatric surgery. However, the outcome of bariatric surgery on psychological health varies between individuals. Comprehensive perioperative mental health evaluation for patients seeking bariatric surgery is important, as psychiatric comorbidities could result in poor outcomes, and based on our knowledge, studies on psychiatric outcomes post bariatric surgery are limited in Saudi Arabia. This study is aimed at assessing the impact of bariatric surgery on developing depression and anxiety symptoms. Methods: Data for this cross-sectional study were collected from patients via an electronic self-administered questionnaire of both genders who underwent bariatric surgery during the period between July 2013 and July 2017 at King Abdulaziz University Hospital (KAUH), Jeddah, Saudi Arabia. Results: The total number of the participants was 214, wherein 66 (30.8%) were males and 150 (69.2%) were females. Participants who underwent bariatric surgery ranged between 17 and 64 years of age with a median age of 36.69 years. With regards to preoperative assessment, we found that 95.8% of our sample did not visit a psychiatry clinic. The postoperative percentage of depression and anxiety among patients was 67 (31.3%) and 40 (18.7%), respectively. Using multivariate regression analysis, patients’ income was found to be significantly associated with anxiety, those who had higher income had less odds of being anxious compared to the group with low income (<3000 riyals) and this was statistically significant. Conclusion: Compared to general population, the post bariatric surgery prevalence of anxiety and depression is high. We recommend pre- and postoperative psychiatric assessment for all bariatric surgery patients in centers where this has not yet been implemented in the pre- and postoperative protocols.